Vitale democratie : Theorie van democratie in actie - Hendriks, Frank (2006)
Democracy is one of the most used and misinterpreted terms of our time. In public discussions concerning the subject it is tacitly assumed that everyone is aware of the meaning of democracy and the implications it carries. In reality democratic ideals and practices take on various forms in various countries. Frank Hendriks sheds light on this subject matter in a comprehensible manner. He distinguishes four ground forms of democracy, which are inherent to democratic forms everywhere. Along with "consensus democracy", Hendriks compares "pendulum democracy", "voter democracy" and "participatory democracy", at national as well as subnational levels of governance. Hendriks concludes in his studies that contrary to popular belief, not one model is superior to the others and calls for a realistic approach to a democracy that is sensitive to the context in which democracy must prove and sustain itself. In Nederland wordt net als elders veel geklaagd over 'het democratisch tekort' en 'de kloof tussen burger en bestuur'. De aangedragen oplossing is doorgaans 'meer democratie'. De consensus op dit punt lijkt groot. Maar de werkelijkheid is anders. Uit een schijnbaar eenvoudig principe, de samentrekking van demos en kratia, het volk dat regeert, vloeien zeer uiteenlopende denk-en handelingswerelden voort. In Vitale democratie werpt Frank Hendriks licht op deze zaak. Hij doet dat in een verhelderend en stimulerend relaas dat op verschillende niveaus kan worden gelezen. Enerzijds schetst Hendriks een panoramisch beeld van wat er in de wereld te koop is aan beproefde modellen van democratie. Anderzijds ontvouwt hij een theoretisch perspectief van waaruit de meervoudige werkelijkheid van de democratie op een zinvolle manier kan worden bekeken, vergeleken en op waarde geschat.